Flow-induced vibration and sound waves of a rotationally oscillating circular cylinder on a nonlinear elastic mount - Liu, Shuai; Qu, Yegao; Gao, Penglin; Meng, Guang (Journal of sound and vibration, 2025)
•Two synchronizations (PLO, TLO) are identified in vortex-induced vibrations.•PLO and TLO patterns are influenced by cubic stiffness and rotating velocity.•Strong nonlinearity alters synchronization and induces separation bubble breaks.•Rotating velocity suppresses quadrupole sound modes.•Nonlinear stiffness triggers higher-order harmonic sound. The paper investigates the flow-induced vibration and sound wave propagation of a rotationally oscillating circular cylinder resting on a nonlinear elastic support and subject to compressible viscous flow with Reynolds number of Re=150 and Mach number of Ma=0.2. An implicitly coupled fluid-structure interaction method based on an arbitrary Lagrangian-Eulerian framework is adopted to predict the dynamic responses of the cylinder. Direct numerical simulations of Navier-Stokes equations are performed to resolve the unsteady flow and sound waves. A nonlinear forced synchronization phenomenon, referred to as ‘lock-on’, occurring between nonlinear vortex-induced vibration and rotational excitation of the cylinder is examined. Two synchronization regions are identified, the primary lock-on and the tertiary lock-on. It is found that the nonlinear elastic mount significantly affects the synchronous patterns of the cylinder by amplifying higher-order harmonic components of the vibration response of the cylinder and altering the separating bubbles in the wake. Moreover, large rotational excitation of the cylinder delays the boundary layer separation, altering the shedding vortex patterns. Asynchronization between the rotational excitation and the vibration of the cylinder modulates the sound waves, while the synchronization produces dipole sound propagation modes containing high-order harmonic wave components.